Stress concentration reduction in an axially loaded rectangular bar with an elliptical hole - Ramírez Monares, José Alfredo; Gamboa Soto, Leonel (Cultura Científica y Tecnológica, 2023)
Two-dimensional finite element analysis was used for stress concentration factors estimation in a wide range of bar-ellipse height and height-width elliptical hole ratios in a tensile bar. Least squares polynomial equations were fit to the design points. These equations agreed and tension stress concentration factor for elliptical holes was described. Such equation reproduces the curves and through its derivative the optimal values that minimize the concentration factor are estimated. The path of the minimal concentration factor was illustrated in a contour plot.